2016
DOI: 10.1021/acs.iecr.5b03499
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Process Operations in Fast-Changing Electricity Markets: Framework for Scheduling with Low-Order Dynamic Models and an Air Separation Application

Abstract: Today's fast-changing markets often require the granularity of production schedules to be refined to time scales comparable to the time constants of a chemical process. Consequently, the process dynamics must be considered explicitly in production scheduling. High dimensionality, nonlinearity, and the associated computational complexity make incorporating dynamic models in scheduling calculations challenging. We propose a novel scheduling approach based on scheduling-oriented low-order dynamic models identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 68 publications
1
136
0
3
Order By: Relevance
“…The latter responses consider electricity spot prices to reduce electrical energy costs. In addition to the economic benefits, environmental impacts, especially carbon footprint, can be mitigated by exploiting electricity with a high share of RES [34,35] electricity-intensive industrial processes such as air separation units (ASU) [36][37][38][39], chlor-alkali (CA) electrolysis [32,40], seawater reverse osmosis [41], and aluminum production processes [42], DSM is particularly worthwhile.…”
Section: Demand Side Managementmentioning
confidence: 99%
“…The latter responses consider electricity spot prices to reduce electrical energy costs. In addition to the economic benefits, environmental impacts, especially carbon footprint, can be mitigated by exploiting electricity with a high share of RES [34,35] electricity-intensive industrial processes such as air separation units (ASU) [36][37][38][39], chlor-alkali (CA) electrolysis [32,40], seawater reverse osmosis [41], and aluminum production processes [42], DSM is particularly worthwhile.…”
Section: Demand Side Managementmentioning
confidence: 99%
“…Potential for economic benefit from integrating process dynamics into design, scheduling, and control problems has also been demonstrated [41,44,52]. Computational reduction of incorporating process dynamics into scheduling has been investigated successfully, maintaining benefit from the incorporation of process dynamics into scheduling while reducing dynamic model order [10,15,16,33,42]. …”
Section: Previous Workmentioning
confidence: 99%
“…Gutierrez-Limon et al demonstrated integrated planning, scheduling, and control responsive to fluctuations in market demand on a CSTR benchmark application [36,37]. Pattison et al investigated ISC with an air separation unit (ASU) in fast-changing electricity markets, responding optimally to price fluctuations [42]. Pattison et al also demonstrated theoretical developments with moving horizon closed-loop scheduling in volatile market conditions [10].…”
Section: Responsiveness To Market Fluctuationsmentioning
confidence: 99%
“…The vast majority of literature concerning the operation of ASUs subject to fluctuating electricity prices accounts for dynamic responses only indirectly by restricting the transitions between quasi‐stationary operating points . Recent work aims at directly accounting for dynamics when making scheduling decisions through the use of low‐order dynamic models, which is also extended to a closed‐loop scheduling formulation . This framework furthermore allows for explicit consideration of the tracking behavior of a subordinated model predictive controller (MPC) in scheduling of ASUs .…”
Section: Introductionmentioning
confidence: 99%